An Overview of Properties and Analytical Methods for Lycopene in Organic Nanocarriers. (3rd October 2021) - Carvalho, Gabriela Corrêa; Sábio, Rafael Miguel; Chorilli, Marlus
Abstract: Lycopene (LYC), a natural compound responsible for the red color of some fruits like pink grapefruit, red guava, watermelon, papaya and, mainly, present in tomatoes ( Solanum lycopersicum ). LYC has been extensively studied because of its various pharmacological properties such as antioxidant, cardioprotective, hypocholesterolemic, antineophasic, photoprotection, antidiabetic and antimicrobial activity. However, LYC uses in therapy is limited due to its insolubility in aqueous solvents, resulting in low bioavailability and stability. In order to overcome these drawbacks, it is essential to use of organic nanocarriers for LYC controlled release. Up to now, the description of LYC-loaded organic nanocarriers are scarce, mainly related to organic nanosystems based on lipid nanostructures such as nanoemulsions (NE), liposomes (LP), niosomes (NI), nanostructured lipid carriers (NLC) and solid lipid nanoparticles (SLN). Taking into account the development of new formulations, is indispensable the use of sensitive and suitable analytical methods previously validated. Among the analytical methods described here, high-performance liquid chromatography (HPLC) stands out due to its good accuracy, precision and desirable detection limit. In this review, we highlights the main biological and physicochemical properties of LYC, as well as LYC-based organic nanocarriers for controlled drug delivery and the analytical methods described in literature to determine LYC in any kind of matrix.